A high perceptual load task reduces thoughts about chocolate, even while hungry. (1st August 2020) - Morris, Jenny; Keith Ngai, Man Yung; Yeomans, Martin R.; Forster, Sophie
Abstract: Intrusive thoughts about food can trigger cravings and result in unhealthy eating behaviour. Here we tested whether Load Theory of attention can be applied to the eating behaviour literature and reduce intrusive appetitive-related thoughts. Load Theory predicts that high levels of perceptual load in a task exhaust attentional capacity and so reduces interference from a range of stimuli, including intrusive thoughts. Therefore, this study aimed to test whether perceptual load reduced appetitive-related intrusive thoughts about chocolate. Sixty female participants were first given a chocolate bar to interact with for 2 min, before rating their levels of hunger, craving and liking for chocolate. They were then asked to avoid thinking about chocolate and instead focus attention on a visual search task. Perceptual load was manipulated within-subjects by varying the search set size. Appetitive-related thoughts were measured using both self-caught and probe-caught measures, allowing us to index load effects at varying levels of meta-awareness. Across subjects, the level of appetitive-related thoughts seen in the high load condition was significantly reduced, to less than half the level seen in the low load condition, on both probe and self-caught measures. Furthermore, self-reported hunger, craving and liking for the chocolate were positively correlated with appetitive-related thoughts under low load, but high perceptual load eliminated these state individual differences. Therefore, engaging in perceptually demanding tasks may be a worthwhile strategy for those wanting to disrupt the cycle of craving at the earliest stage.